2008
DOI: 10.1098/rspb.2008.1473
|View full text |Cite
|
Sign up to set email alerts
|

Marine mammals through time: when less is more in studying palaeodiversity

Abstract: The validity of biological explanations of patterns of palaeodiversity has been called into question owing to an apparent correlation of diversity with the amount of sedimentary rock preserved. However, this claim has largely been based on comprehensive estimates of global marine Phanerozoic diversity, thus raising the question of whether a similar bias applies to the records of smaller, well-defined taxonomic groups. Here, new data on European Caenozoic marine sedimentary rock outcrop area are presented and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Following a preliminary comparison by Uhen and Pyenson [59], Marx [60] found that sirenian richness through time did not parallel European richness of cetaceans or pinnipedimorphs (while accounting for possible biases, such as rock outcrop area), which suggested that the peaks and drops in richness of the sirenian fossil record likely reflect secular biological signals. Because sirenian are intimately tied with nearshore habitats (specially epicontinental surfaces), it is possible that their richness reflects the effects of eustatic sea-level change.…”
Section: Discussionmentioning
confidence: 99%
“…Following a preliminary comparison by Uhen and Pyenson [59], Marx [60] found that sirenian richness through time did not parallel European richness of cetaceans or pinnipedimorphs (while accounting for possible biases, such as rock outcrop area), which suggested that the peaks and drops in richness of the sirenian fossil record likely reflect secular biological signals. Because sirenian are intimately tied with nearshore habitats (specially epicontinental surfaces), it is possible that their richness reflects the effects of eustatic sea-level change.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating Phanerozoic palaeodiversity have used a number of proxies for sampling, including outcrop area (Smith 2001;Crampton et al 2003;Smith & McGowan 2005, 2007Mander & Twitchett 2008;Marx 2009;Wall et al 2009;Peters & Heim 2010;Dunhill et al 2012), sedimentary rock volume (Raup 1972(Raup , 1976Kalmar & Currie 2010;Dunhill et al 2012), and palaeontological worker effort (Sheehan 1977;Purnell & Donoghue 2005;Dunhill et al 2012). In this study we have compared the fossil record of the Triassic of England and Wales with a number of sampling proxies.…”
Section: The Validity Of Sampling Of Proxiesmentioning
confidence: 98%
“…Almost all published studies investigating the adequacy of the fossil record have been carried out on a global (Raup 1972(Raup , 1976Lloyd et al 2008; Barrett et al 2009;Butler et al 2009Butler et al , 2010Wall et al 2009;Benson et al 2010) or continental scale (Smith 2001;Peters 2005Peters , 2006Smith & McGowan 2005, 2007Marx 2009;Peters & Heim 2010, where both the fossil occurrence data and sampling proxies are often, at best, vague approximations (Twitchett et al 2000;Crampton et al 2003;Benton 2010;Benton et al 2011;Dunhill 2011Dunhill , 2012Lloyd et al 2011;Dunhill et al 2012). The majority of these large-scale studies have discovered positive correlations between palaeodiversity and sampling proxies.…”
mentioning
confidence: 93%
“…Crampton et al 2003;Smith & McGowan 2007;Alroy et al 2008;McGowan & Smith 2008;Wall et al 2009). There have also been several studies of marine vertebrate diversity (Uhen & Pyenson 2007;Marx 2009;Benson et al 2010;Marx & Uhen 2010;. Although 'sampling-corrected' studies of terrestrial organismal diversity (typically vertebrates) remain scarce, a number of analyses have appeared recently, focusing on Permo-Triassic vertebrates (Benton et al 2004), anomodont synapsids (Fröbisch 2008), dinosaurs (Sereno 1997(Sereno , 1999Weishampel & Jianu 2000;Fastovsky et al 2004;Carrano 2005Carrano , 2008aUpchurch & Barrett 2005;Wang & Dodson 2006;Lloyd et al 2008;Barrett et al 2009;Butler et al 2011;, pterosaurs (Butler et al 2009) and Cenozoic mammals (Alroy 2000).…”
mentioning
confidence: 98%